Impacts of Menstrual Attitudes, Premenstrual Syndrome and Stress on Burnout among Clinical Nurses - Ji Hye Hwang; Mi Hae Sung (Korean Society of Women Health Nursing, 2016)
PURPOSE: The purpose of this study was to investigate factors which effect clinical nurses' exhaustion. METHODS: This research was conducted targeting 140 clinical nurses. Data were collected from 18 September to 30 September 2015. Data were analyzed using the program SPSS/WIN 18.0. Descriptive statistics, t-test, ANOVA, Pearson correlation coefficient, and Stepwise multiple regression analysis were used. RESULTS: Burnout was significantly different by age (F=7.99, p=.001), marital status (t=8.69, p=.004), department area (F=7.65, p<.001), frequency of night work in a month (F=7.65, p=<.001), and clinical career (F=3.68, p=.028). There was positive correlations between menstrual attitudes of participants and premenstrual syndrome (r=34, p<.001), menstrual attitudes and stress (r=.40, p<.001), and menstrual attitudes and burnout (r=.16, p=.031). There were positive correlations between premenstrual syndrome and stress (r=.46, p<.001), between premenstrual syndrome and burnout (r=.35, p<.001), and between stress and burnout (r=.36, p<.001). Factors influencing burnout were premenstrual syndrome (β=.335) and age (β=.216), with an explanatory power of 18.0%. CONCLUSION: There is a need to develop and apply program for reducing clinical nurses' pre-menstrual syndrome. In addition, policies are needed to allow for menstruation leave, thereby making it legal.